Object oriented PHP and MVC - Traversy, Brad (Packt Publishing, 2018)
"In this course, we will go step by step to build a complete custom MVC (Model View Controller) framework Called TraversyMVC using object-oriented PHP. We will build something similar to Codeigniter but much lighter. This framework is a completely open source and you are free to change the name, add stuff, etc and use it as your own. This framework will include. A core library class to load controllers & methods from the URL (Also using .htaccess). Not only will we create the framework but we will build an application on top of it called SharePosts which will be somewhat of a social network to share posts. This application will include: Full user authentication, Access control for posts, Server-side form validation Bootstrap 4 UI, Posts CRUD, Helper functions (flash messaging & redirects). We will also be deploying the application to the Internet."--Resource description page